Targeting pathophysiological rhythms: prednisone chronotherapy shows sustained efficacy in rheumatoid arthritis. Issue 7 (11th June 2010) - Buttgereit, Frank; Doering, Gisela; Schaeffler, Achim; Witte, Stephan; Sierakowski, Stanislaw; Gromnica-Ihle, Erika; Jeka, Slawomir; Krueger, Klaus; Szechinski, Jacek; Alten, Rieke
Abstract : Objective: This 9-month open-label extension of the Circadian Administration of Prednisone in Rheumatoid Arthritis Study (CAPRA 1) investigated the long-term safety and efficacy of prednisone chronotherapy with a novel modified-release (MR) prednisone for up to 12 months. Methods: Of 288 patients with rheumatoid arthritis originally randomised to MR or immediate-release (IR) prednisone, 249 continued with prednisone chronotherapy (2–10 mg/day) in the 9-month open-label extension. Duration of morning stiffness of the joints (MS), disease activity scores (DAS28), American College of Rheumatology (ACR20) responses and plasma levels of interleukin 6 (IL-6) were assessed. Safety was analysed from adverse event reports and laboratory investigations. Results: During the 3-month double-blind phase, patients in the MR group achieved a reduction in MS of 33.1% while no change was observed in the IR group. After 6 months of treatment, MS was reduced in the IR/MR group by 54% and in the MR/MR group by 56%. MS reduction after 12 months was 45% (IR/MR group) and 55% (MR/MR group). Plasma levels of IL-6 declined on MR treatment. DAS28 was reduced from 5.8 to 4.8 (MR/MR group) and 4.9 (IR/MR group), respectively. 37% of the 219 patients who completed the 12-month study achieved improvement according to the ACR20 criteria. Adverse events did not differ from the known profile of low-dose prednisone. Conclusions: Prednisone chronotherapy with the MR tablet was safe and well tolerated and provided a sustained improvement which resulted in a better benefit to risk ratio of low-dose glucocorticoid treatment for at least 12 months.